Ecotoxicological and Risk Assessment of Hydroquinone Cream Residue on Duckweed Plants - Adebayo , G. B.; Orimolade, B. O.; Okoro , H. K.; Banwo , M.A. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Residues from personal care products have been reportedly found in soils and are harmful to plants and animals. This research studied the ecotoxicology effects and risk assessment of hydroquinone cream residue on duckweed plant. The effects of different concentrations (50, 100, 150 and 250 ppm) on the duckweed (Lemna minor) were used for the study. The duckweed was collected from the Dam area of University of Ilorin, Ilorin, Nigeria and cultured for a period of one week before using it for the study. The plants were exposed to the different concentrations of hydroquinone cream for a period of 8 days. The results revealed that all the concentration shows adverse effect on the plant pigment content as well as biomass with the effect increasing as the concentration increases. The study has shown that the residue of hydroquinone cream could be dangerous to the ecosystem at concentration as low as 50 ppm which is well below the amount of the residue expected in the environment.